Antioxidant Activity of Sprouting Mungbean (Vigna radiata) Variety VIMA-1 - Puyanda, Irvia Resti; Kuswanto, Kapti Rahayu; Margareta, Laurensia Atha; Anggraini, Metha Putri Agustyn (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2022)
The objectives of this work were to investigate the influence of germination times (24, 48, 72, 96, and 120 hours) and conditions (light and dark conditions) on the antioxidant activity and total phenolic compounds in mungbean sprout. Antioxidant activity and total phenolic content were analyzed using in vitro methods, with the antioxidant activity assessed using ABTS and DPPH methods. We observed a significant increase (p < 0.05) in antioxidant activity using the ABTS method, which decreased after 48 hours of germination. In contrast, the DPPH method showed a significant decrease (p < 0.05) followed by an increase in antioxidant activity after 48 hours of germination. Meanwhile, germination up to 48 hours significantly reduced (p < 0.05) the total phenoliccontent in both conditions, while against that time, it increased significantly (p < 0.05) up to 96 hours. The effects of germination time and conditions were significant (p < 0.05) for both antioxidant activities and total phenolic content. Generally, germination under dark conditions resulted in lower antioxidant activities and total phenolic content during the germination process